👤

Va rog frumos sa ma ajutati!

Va Rog Frumos Sa Ma Ajutati class=
Va Rog Frumos Sa Ma Ajutati class=

Răspuns :

[tex]5)a)(x + 1)(x + 8) [/tex]

[tex] = {x}^{2} + 8x + x + 8[/tex]

[tex] = {x}^{2} + 9x + 8[/tex]

[tex]b)(x - 5)(x + 7)[/tex]

[tex] = {x}^{2} + 7x - 5x - 35[/tex]

[tex] = {x}^{2} + 2x - 35[/tex]

[tex]c)(3x + 1)(3x + 5)[/tex]

[tex] = 9 {x}^{2} + 15x + 3x + 5[/tex]

[tex] = 9 {x}^{2} + 18x + 5[/tex]

[tex]d)(2x + 1)(x - 3)[/tex]

[tex] = {2x}^{2} - 6x + x - 3[/tex]

[tex] = 2 {x}^{2} - 5x - 3[/tex]

[tex]e)( - x + 2)(3x + 4)[/tex]

[tex] = - 3 {x}^{2} - 4x + 6x + 8[/tex]

[tex] = - 3 {x}^{2} + 2x + 8[/tex]

[tex]f)(x - 1)( {x}^{2} + 5)[/tex]

[tex] = {x}^{3} + 5x - {x}^{2} - 5[/tex]

[tex]g)( - 3x + 5)( {x}^{3} + 1)[/tex]

[tex] = - 3 {x}^{4} - 3x + 5 {x}^{3} + 5[/tex]

[tex]h)( {x}^{2} + 2xy)(x - y)[/tex]

[tex] = {x}^{3} - {x}^{2} y + 2 {x}^{2} y - 2x {y}^{2} [/tex]

[tex] = {x}^{3} + {x}^{2} y - 2x {y}^{2} [/tex]

[tex]i)( - x + 4)( - y + 3)[/tex]

[tex] = xy - 3x - 4y + 12[/tex]

[tex]j)(0.5x + 1)(2x - 3)[/tex]

[tex] = {x}^{2} - 1.5x + 2x - 3[/tex]

[tex] = {x}^{2} + 0.5x - 3[/tex]

[tex]k)a(a + 2)(3a + 4)[/tex]

[tex] = ( {a}^{2} + 2a)(3a + 4)[/tex]

[tex] = 3 {a}^{3} + 4 {a}^{2} + 6 {a}^{2} + 8a[/tex]

[tex] = 3 {a}^{3} + 10 {a}^{2} + 8a[/tex]

[tex]l)( {a}^{2} + 2a + 3)(a - 1)[/tex]

[tex] = {a}^{3} - {a}^{2} + 2 {a}^{2} - 2a + 3a - 3[/tex]

[tex] = {a}^{3} + {a}^{2} + a - 3[/tex]

[tex]m)(x - y) ({x}^{2} + xy + {y}^{2} )[/tex]

[tex] = {x}^{3} + {x}^{2} y + x {y}^{2} - {x}^{2} y - x {y}^{2} - {y}^{3} [/tex]

[tex] = {x}^{3} - {y}^{3} [/tex]
[tex]n)(x + 1)( {x}^{2} - x + 1)[/tex]

[tex] = {x}^{3} - {x}^{2} + x + {x}^{2} - x + 1[/tex]

[tex] = {x}^{3} + 1[/tex]

[tex]o)(x - 1)( {x}^{2} + x + 1)[/tex]

[tex] = {x}^{3} + {x}^{2} + x - {x}^{2} - x - 1[/tex]

[tex] = {x}^{3} - 1[/tex]

[tex]p)(a + 2)( {a}^{2} - 2a + 4)[/tex]

[tex] = {a}^{3} - 2 {a}^{2} + 4a + 2 {a}^{2} - 4a + 8[/tex]

[tex] = {a}^{3} + 8[/tex]

[tex]r)(x + 3)(x - 1)(1 - x)[/tex]

[tex] = ( {x}^{2} - x + 3x - 3)(1 - x)[/tex]

[tex] = {x}^{2} - {x}^{3} - x + {x}^{2} + 3x - 3 {x}^{2} - 3 + 3x[/tex]

[tex] = - {x}^{3} - {x}^{2} + 5x - 3[/tex]

[tex]s)( - y + 8)(x + 1)(x - 1)[/tex]

[tex] = ( - y + 8)( {x}^{2} - 1)[/tex]

[tex] = - {x}^{2} y + y + 8 {x}^{2} - 8[/tex]

[tex]6)1)( \sqrt{3} + \sqrt{2} ) \times \sqrt{2} [/tex]

[tex] = \sqrt{6} + 2[/tex]

[tex]2)( \sqrt{3} - \sqrt{4} )(1 + \sqrt{2} )[/tex]

[tex] = ( \sqrt{3} - 2)(1 + \sqrt{2} )[/tex]

[tex] = \sqrt{3} + \sqrt{6} - 2 - 2 \sqrt{2} [/tex]

[tex]3)(3 + \sqrt{2} )(1 + \sqrt{2} )[/tex]

[tex] = 3 + 3 \sqrt{2} + \sqrt{2} + 2[/tex]

[tex] = 5 + 4 \sqrt{2} [/tex]

[tex]4)( \sqrt{8} + \sqrt{2} )(1 + \sqrt{2} )[/tex]

[tex] = (2 \sqrt{2} + \sqrt{2} )(1 + \sqrt{2} )[/tex]

[tex] = 3 \sqrt{2} (1 + \sqrt{2} )[/tex]

[tex] = 3 \sqrt{2} + 3 \times 2[/tex]

[tex] = 3 \sqrt{2} + 6[/tex]

[tex]5)( - \sqrt{3} + \sqrt{2} )(1 + \sqrt{2} )[/tex]

[tex] = - \sqrt{3} - \sqrt{6} + \sqrt{2} + 2[/tex]

[tex]6)( \sqrt{3} - \sqrt{15} )(1 + \sqrt{5} )[/tex]

[tex] = \sqrt{3} + \sqrt{15} - \sqrt{15} - \sqrt{75} [/tex]

[tex] = \sqrt{3} - \sqrt{75} [/tex]

[tex] = \sqrt{3} - 5 \sqrt{3} [/tex]

[tex] = - 4 \sqrt{3} [/tex]

[tex]7)(2 \sqrt{3} - \sqrt{2} )(3 - \sqrt{2} )[/tex]

[tex] = 6 \sqrt{3} - 2 \sqrt{6} - 3 \sqrt{2} + 2[/tex]